2024
DOI: 10.3389/fmicb.2024.1354696
|View full text |Cite
|
Sign up to set email alerts
|

A bacteriophage cocktail can efficiently reduce five important Salmonella serotypes both on chicken skin and stainless steel

Tamar Gvaladze,
Hansjörg Lehnherr,
Stefan Hertwig

Abstract: Salmonella is one of the most important zoonotic pathogens and is mostly transmitted through food of animal origin. Application of bacteriophages is a promising tool to biocontrol Salmonella on both food and food contact surfaces. In this study, we evaluated the effectiveness of a six-phage cocktail for the reduction of Salmonella Enteritidis and a mixture of five major Salmonella serotypes (S. Enteritidis, Salmonella Typhimurium, Salmonella Infantis, Salmonella Paratyphi B, and Salmonella Indiana) on chicken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…For instance, treatment of contaminated chicken breast with a cocktail of five phages at MOI = 10 4 reduced the number of Salmonella Typhimurium by 2.0, 1.9, and 2.2 log CFU/piece at 2, 4, and 6 h, respectively 4 , 22 . Gvaladze et al, 2024 sprayed a cocktail of six phages on chicken skin contaminated with Salmonella Enteritidis and the mixed culture and achieved after 30 min a significant 1.8 log and 1 log reduction, respectively 55 . Spricigo et al, 2013 observed that dipping chicken breast for five minutes in a solution containing the bacteriophage cocktail and subsequently chilled at 4 °C for seven days showed significant 2.2 and 0.9 log10 cfu/g reductions in the concentrations of Salmonella Typhimurium and Salmonella Enteritidis, respectively 56 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, treatment of contaminated chicken breast with a cocktail of five phages at MOI = 10 4 reduced the number of Salmonella Typhimurium by 2.0, 1.9, and 2.2 log CFU/piece at 2, 4, and 6 h, respectively 4 , 22 . Gvaladze et al, 2024 sprayed a cocktail of six phages on chicken skin contaminated with Salmonella Enteritidis and the mixed culture and achieved after 30 min a significant 1.8 log and 1 log reduction, respectively 55 . Spricigo et al, 2013 observed that dipping chicken breast for five minutes in a solution containing the bacteriophage cocktail and subsequently chilled at 4 °C for seven days showed significant 2.2 and 0.9 log10 cfu/g reductions in the concentrations of Salmonella Typhimurium and Salmonella Enteritidis, respectively 56 .…”
Section: Discussionmentioning
confidence: 99%